FRIENDLY COMPETITION – GREEK-SERBIAN RELATIONS AND OTTOMAN MACEDONIA IN THE EIGHTIES OF THE 19TH CENTURY (Annual of the Faculty of Philosophy in Skopje, 2019)
The purpose of this paper is to demonstrate the contacts between two Balkanstates - Serbia and Greece and their proper attempt to reach an agreement on the divisionof the Ottoman Macedonia into spheres of interest. The talks of the two countries,that had an alliance agreement as of 1867, were taking place on several levels.Officially between diplomats and politicians and unofficially between diplomats andintellectuals. Although in Greece it was considered that some kind of an agreementcould be reached with Serbia over Macedonia, given the weaker position of the Serbianside, the initial findings of the research show that it was very difficult. Bothsides had claims to the same region. Athens initially thought that Serbian claims didnot relate to those parts of Macedonia to which Greece had claims, but quickly foundthat the interests of Serbs entered much more to the south than Greek expectations.On the other hand, Belgrade was aware that Serbia's interests would not be realisedif they did not have some agreement with Greece. Both sides were friendly towardone another, but their interests were different and competitive.
Keywords: GREECE; SERBIA; MACEDONIA; NEGOTIATIONS; SPHERES OF INTEREST